2009
DOI: 10.1002/jmv.21687
|View full text |Cite
|
Sign up to set email alerts
|

Detection of varicella‐zoster virus DNA in 414 human trigeminal ganglia from cadavers by the polymerase chain reaction: A comparison of the detection rate of varicella‐zoster virus and herpes simplex virus type 1

Abstract: Investigation of varicella-zoster virus (VZV) is important epidemiologically, and determination of its prevalence rate in human trigeminal ganglia is important to provide surveillance data. To date, studies on VZV detection in trigeminal ganglia have used specimens obtained from a relatively limited number of cadavers. This study attempted to detect VZV DNA as well as Herpes simplex virus type 1 (HSV-1) DNA by the polymerase chain reaction (PCR) from 414 samples of trigeminal ganglia obtained from 207 cadavers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Data from a recent large study (n = 414 TG from 207 cadavers) conducted in Japan show that the incidence of HSV-1 infection increases with age. Furthermore, this study revealed that nearly all people greater than 60 years old harbor latent HSV-1 in the TG [27] and complements an earlier study ( n = 242 TG from 121 cadavers) indicating similar age-based trends in HSV-1 infection in the TG in Japan [28]. One large study from Germany ( n = 109 cadavers) also supports age-based trends in the incidence of HSV-1 infection [29].…”
Section: Epidemiologic Insightssupporting
confidence: 80%
“…Data from a recent large study (n = 414 TG from 207 cadavers) conducted in Japan show that the incidence of HSV-1 infection increases with age. Furthermore, this study revealed that nearly all people greater than 60 years old harbor latent HSV-1 in the TG [27] and complements an earlier study ( n = 242 TG from 121 cadavers) indicating similar age-based trends in HSV-1 infection in the TG in Japan [28]. One large study from Germany ( n = 109 cadavers) also supports age-based trends in the incidence of HSV-1 infection [29].…”
Section: Epidemiologic Insightssupporting
confidence: 80%
“…In a comparative study on viral presence in trigeminal ganglia from cadavers, VZV was detected in 97% and HSV-1 in 65% of the subjects [23]. While HSV-1 may reactivate frequently (up to monthly in some cases) to cause oral herpes, the reactivation of VZV in form of herpes zoster seldom occurs more than once in a lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both VZV and HSV are widespread human pathogens, with about 60 to 90% of the population latently infected by both viruses by adulthood (19). It has been reported that both viruses can reside latently in the same trigeminal ganglion (19)(20)(21)(22), and evidence from in situ hybridization suggests the rare presence of both HSV1 and VZV genomes in the same cells (23). However, the ability of both viruses to productively infect the same neuron has not been investigated.…”
mentioning
confidence: 99%